Attitude, Risk Perception and Readiness of Ethiopian Potential Migrants and Returnees Towards Unsafe Migration - Minaye, Abebaw; Zeleke, Waganesh A. (African Human Mobility Review, 2021)
In Ethiopia, where there is high prevalence of migration to the Middle East and Europe, a multitude of studies have focused on the relationships between the role of smugglers, push and pull factors, and illegal migration. However, only a fraction of studies have examined the context from the individual and collective mind-set perspective. The process of the decision to migrate may be influenced by individuals’ beliefs about illegal migration. This study examined the attitudes, levels of readiness and risk perceptions of potential and returnee migrants towards illegal migration to the Middle East. Survey data were collected from 1,726 Ethiopian returnee (n=991) and potential migrants (n=735). Results indicated that here was a significant difference between potential and returnee migrants in holding a positive attitude towards unsafe and illegal migration, t (1260) =-8.474, p=0.000.